Analisis Perwilayahan Komoditas Kedelai di kabupaten Jember - Linda Eka Dewi; Ardhitya Alam Wiguna (Jurnal Ilmiah Inovasi, 2017)
In the province of East Java, Jember Regency is sixth largest soybean producer with total production are 25.178 tons in the 2015. Soybean Commodities in Jember Regency was an area harvested in 2015 covered an area of 12.238 Ha spread over several districts in Jember Regency. This research was intended to determine the soybean centers on Jember Regency, distribution characteristics of soybean comodities in the bases sector regional of Jember Regency, and the role of soybean comodities in supporting of agricultural sector in Jember Regency. The analysis methods used in this research were Location Quotient (LQ) analysis, lokalita analysis and specialization analysis of soybean commodities, as well as Analysis ofÂ  Basic Service Ratio (BSR), Regional Multiplier (RM), and Short Multiplier. Results Location Quotient (LQ) Analysis showed that the base area of soybean comodities based on indicators of harvested area consists of 10 subdistricts they were: Bangsalsari Sub District, Umbulsari, Jombang, Balung, Rambipuji, Ajung, Kaliwates, Kencong, Jenggawah, and Ambulu Sub District. Soybean commodities base area based on indicators of production consists of 9 subdistricts they were: Bangsalsari Sub District, Umbulsari, Balung, Rambipuji, Jombang, Ajung, Kaliwates, Kencong, and Jenggawah Sub District. Commodities soybean farming in Jember Regency were not concentrated in one area, but spread across several districts in Jember Regency, and were not specialized in soybeans commodity farm. Commodities soybean farming in Jember Regency also could participate in support the agricultural sectors of food crops in Jember Regency.